Investigation of Environmental Determinants for Agritourism Development in Almaty Region of Kazakhstan - Roman Plokhikh; Fodor Gyula; Aiman Shaken; Berghauer Sándor; Aliya Aktymbayeva; Tóth Attila; Miroslaw Mika; Dávid Lóránt Dénes; Фодор Дюло; Бергхауер Олександр; Товт Атілла; Давід Лорант Денеш (Editurii Universității din Oradea, 2022)
Abstract. This study aims to comprehend relations between environmental determinants and agritourism by example of the Almaty region of Kazakhstan. As a basis for the research of this specific content the representation about agrarian recreational-tourist complexes (ARTCs) was developed and applied (ARTCs are special territorial and intersectoral integrities which largely depend on environmental determinants). Agritourism development is presented as the most important prerequisite for different successful tourism activities in Kazakhstan. With use of the developed instruments, information of different types and cartographical data 15 ARTCs were identified within the Almaty region as well as the influence of the environmental determinants for agritourism was studied. In bare outlines, the methods of functional agritourism and ecological agritourism analysis of the ARTCs’ territory based on analysis of the environmental determinants are described. The results of the research can be used for the establishment of prospects for agritourism development within the ARTCs as well as for the development of address recommendation system.
Keywords: agritourism; environmental determinants; complex; assessment; Kazakhstan